The problem of how Xavier Zubiri’s thought has been received in Colombia - Pachón Soto, Damián (Estudios de Filosofía, 2012)
In this paper I show some of the causes behind the lack of attention paid to Xavier Zubiri´s philosophical thought in Colombia, such as, the fact that his work was not published which meant the absence of discussion of his ideas. At the same time, the short influence of Zubiri on exiled philosophers in 1939. Others causes were Ortega & Gasset’s influence in Latin America which shadowed Zubiri; the phobia for Spanish thought created by universalist philosophers, and the existence of an uncritical cult in confessional universities. I explain the historical reasons behind the limited critical attention and I propose ways to overcome said difficulties so as to expand the horizons of our philosophy.